Análisis comparativo de herramientas de CLOUD COMPUTING HYPER-V Y VMWARE aplicada a una propuesta de implementación de CLOUD privada para la Cooperativa de Ahorro y Crédito Riobamba Ltda. Agencia Guano. - Barbecho Hidalgo, Jorge Luis (2016)
This research project will allow the implementation of private "Cloud" developed to “Cooperativa de Ahorro y Crédito Riobamba Ltda” Guano Agency. This research displays a study and analysis of the main features of the following software tools: VMware and Hyper-V; in order to compare and select the best alternative to create a private "Cloud" in order to store information. It is important mention that was used a physical computer to test the above hypervisors to create virtual machines. As a result of analysis tools for private "Cloud" "Own Cloud" got 100%, with 84.6% Pydio like Sea File. The comparison results of monitors are: VMware with 100% is the hypervisor that best meets the requirements, Hyper-V with 85.7%. In conclusion VMware is the hypervisor that allows virtual machines to create powerful and consume less resources. "OwnCloud" is the free tool that offers unlimited storage and more features for free to users. "VMware" is recommended to display the "OwnCloud" application, so employees of the “Cooperativa de Ahorro y Crédito Riobamba Ltda” Guano Agency can use it. And I this way ensure the availability, privacy and ownership of the stored data.